2018
DOI: 10.1071/cp17202
|View full text |Cite
|
Sign up to set email alerts
|

Sodium silicate and calcium silicate differentially affect silicon and aluminium uptake, antioxidant performance and phenolics metabolism of ryegrass in an acid Andisol

Abstract: Evidence indicates that silicon (Si) alleviates diverse stresses by improving the antioxidant capacity and phenolics metabolism of plants. We assessed the effect of sodium silicate (Na2SiO3) and calcium silicate (CaSiO3) on Si and aluminium (Al) uptake, antioxidant performance and phenolics (with antioxidant or structural function) of ryegrass cultivated on an acid Andisol under greenhouse conditions. Ryegrass was treated with either sodium silicate or calcium silicate at gradually increasing doses (250, 500 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
4
23
0
Order By: Relevance
“…There are evidences have shown that Si can counteract the effects of excess of certain metals (e.g., Zn, Fe, Cu, Cd, Cr, Mn, As) [10,[38][39][40][41][42] by promoting: (i) cell wall-binding [10], (ii) modification of gene expression of PAL enzyme [38], (iii) phenotypical structural alterations that increase root length [39], (iv) changes to the number of leaves per plant and leaf area [40], and (v) changes to the thickness of epidermal layers of the leaf [41]. With respect to Al toxicity in particular, some studies have proposed that Si may reduce plant stress by promoting: (i) increases in the solution pH [43], (ii) the formation of aluminosilicates in the growth media and cell wall [43,65,66], (iii) the release of phenolic compounds by the root tips [47,60], (iv) increment of carotenoids and chlorophyll in leaves [67], and (v) stimulation of antioxidant enzyme activities and antioxidant compound production [23,44]. Nevertheless, there is still a controversial debate regarding the mechanisms implicated in the Si-mediated the attenuation of Al toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are evidences have shown that Si can counteract the effects of excess of certain metals (e.g., Zn, Fe, Cu, Cd, Cr, Mn, As) [10,[38][39][40][41][42] by promoting: (i) cell wall-binding [10], (ii) modification of gene expression of PAL enzyme [38], (iii) phenotypical structural alterations that increase root length [39], (iv) changes to the number of leaves per plant and leaf area [40], and (v) changes to the thickness of epidermal layers of the leaf [41]. With respect to Al toxicity in particular, some studies have proposed that Si may reduce plant stress by promoting: (i) increases in the solution pH [43], (ii) the formation of aluminosilicates in the growth media and cell wall [43,65,66], (iii) the release of phenolic compounds by the root tips [47,60], (iv) increment of carotenoids and chlorophyll in leaves [67], and (v) stimulation of antioxidant enzyme activities and antioxidant compound production [23,44]. Nevertheless, there is still a controversial debate regarding the mechanisms implicated in the Si-mediated the attenuation of Al toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Over recent years, it has been shown that Si enhances the primary metabolism by improving photosynthesis [11,16,17] and nutrient uptake [18], as well as the secondary metabolism through stimulation of the production of phenolic compounds with either antioxidant (e.g., flavonoids) or structural (e.g., lignin) functions [19][20][21]. Therefore, it has been reported that Si causes improvement in either antioxidant or structural phenols metabolism of plants under stressful environmental conditions [19,20,22,23]. This occurs via the regulation of the transcript level or activity of enzymes involved to phenylpropanoid pathway (e.g., phenylalanine ammonia lyase, peroxidase) [23][24][25], formation of lignin-carbohydrate complexes [26,27], and direct complexation of Si with polyphenolic compounds [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations